Unusual presentation of a neuroepithelial cyst: A case report - Fallis Desita, MD; Widiana Ferriastuti, MD; Dyah Fauziah, MD (Radiology Case Reports, 2022)
Neuroepithelial cysts are benign, congenital, ependymal-lined cysts that constitute an infrequent cause of neurological symptoms among intracranial cystic lesions. We present Indonesian patient who underwent brain MRI depicting neuroepithelial cysts and pathological examination confirmed. Surgery was performed and yielded a satisfying result. Awareness of the entity and specific imaging features is key to making the diagnosis of neuroepithelial cyst and commencing appropriate treatment. This report is expected to aid in the diagnosis of neuroepithelial cysts, which are rare, and reduce the occurrence of misdiagnosis.